Analisis Efektivitas dan Kontribusi Pajak Restoran, Pajak Hotel, dan Pajak Hiburan Serta Pajak Bumi dan Bangunan Perdesaan dan Perkotaan (PBB P2) Terhadap Pendapatan Asli Daerah (PAD) - Marhani, Yollanda (Syntax Corporation, 2026)
The revenue source that contributes most to local first-year earnings in the city of Padang is municipal taxes from Regional Original Revenue. Taxes collected both in urban and rural areas include land and building taxes (PBB P2), hotels, entertainment and restaurants. This study aims to determine the effectiveness and contribution of restaurant tax, hotel tax, entertainment tax, as well as rural and urban land and building tax (PBB P2) in Padang City varies greatly during 2018- 2021. This research method uses quantitative methods or as numerical values and using descriptive techniques that begin with data collection and end with data analysis and use saturated samples. The Padang City Regional Revenue Agency (Bappenda) provided the data used in this study. The results of this study indicate that the level of effectiveness is above 100%. This is because the Municipal Government of Padang has succeeded in achieving its tax revenue target. Then the restaurant tax and hotel tax have a positive effect on local revenue in 2018-2021, while the entertainment tax and rural and urban land and building tax (PBB P2) have a negative effect in 2018-2021. entertainment and PBB P2 Padang City in 2018-2021 is less effective because the percentage contribution annually is less than 20%.